The Retail-Led Transformation of Agrifood Systems and its Implications for Development Policies - Reardon, Thomas; Berdegué, Julio A. (Washington, DC: World Bank, 2012)
The "supermarket revolution" has led to a profound and rapid transformation of the food industry in developing countries. This paper examines the impacts on consumers and traditional retailers (downstream in the agrifood system) and processors, wholesalers and farmers (upstream in the system).